2020
DOI: 10.1080/02640414.2020.1788288
|View full text |Cite
|
Sign up to set email alerts
|

A real-time feedback method to reduce loading rate during running: Effect of combining direct and indirect feedback

Abstract: Impact loading plays a key role in the pathophysiology of running-related injuries. Providing real-time feedback may be an effective strategy to reduce impact loading; however, it is currently unclear what an effective training method to help runners achieve a habitual low loading rate is. We subjected 20 healthy non-runners to a structured sequence of direct and indirect biofeedback designed to facilitate broader exploration of neuro-mechanical workspace for potential movement solutions (indirect feedback on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…The results of the Downs and Black Quality Index scores for each study are shown in Table 2 . Of the 37 included studies, 17 were high quality [ 22 , 27 42 ], 19 were moderate quality [ 23 , 25 , 26 , 43 58 ], and 1 was low quality [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…The results of the Downs and Black Quality Index scores for each study are shown in Table 2 . Of the 37 included studies, 17 were high quality [ 22 , 27 42 ], 19 were moderate quality [ 23 , 25 , 26 , 43 58 ], and 1 was low quality [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…This aligns well with the idea (expressed in previous section) that a training intervention should create the condition for workers to develop their own understanding of and solution(s) to improve movement to reduce their spine flexion. Furthermore, this strategy likely results in the exploration and stabilization of different movement solutions that can adapt to changes in working circumstances (for examples see Pacheco et al, 2019 ; Garofolini et al, 2020 ).…”
Section: Deliberate Practice Framework and Principles Of Motor Learning For Designing A Training Intervention: A Theoretical Perspectivementioning
confidence: 99%